Low level of mono(2-ethylhexyl) phthalate reduces oocyte developmental competence in association with impaired gene expression. (15th February 2017) - Kalo, D.; Roth, Z.
Highlights: Low doses of MEHP impair oocyte developmental competence and transcript expression A prominent effect of MEHP was found when oocytes were cultured in the absence estradiol. Although it was the oocyte that was exposed to MEHP, effects were carried over to the blastocyst stage. The findings suggest that low levels of phthalate must be taken into consideration in risk assessments. Abstract: Di-(2-ethylhexyl) phthalate (DEHP) and its metabolite, mono-(2-ethylhexyl) phthalate (MEHP), are reproductive toxicants. However, disruptive effects of MEHP at low concentrations on the oocyte and developing blastocyst are unknown. Previously, we detected low levels of MEHP in follicular fluid aspirated from DEHP-treated cows associated with reduced estradiol levels. Moreover, the MEHP concentrations found were similar to those reported for follicular fluid aspirated from women who have undergone IVF cycles. In the current study, we used an in vitro embryo production model to examine the effect of MEHP at low levels on oocyte developmental competence. We set up several experiments to mimic the follicular fluid content, i.e., low MEHP level and low estradiol. For all experiments, cumulus oocyte complexes (COCs) were aspirated from bovine ovaries, then matured in vitro in standard oocyte maturation medium (OMM) supplemented with: MEHP at a range levels (20–1000 nM) or with estradiol at a range levels (0–2000 ng/ml). Then, oocytes were fertilized and cultured for an additional 7 days to allow blastocyst development. Findings revealed that MEHP at low levels impairs oocyte developmental competence in a dose-dependent manner ( P < 0.05) and that estradiol by itself does not impair it. Accordingly, in another set of experiments, COCs were matured in vitro with MEHP at two choosen concentrations (20 or 1000 nM) with or without estradiol, fertilized and cultured for 7 days. Samples of mature oocytes and their derived blastocysts were subjected to quantitative real-time PCR to examine the profiles of selected genes ( CYC1, MT-CO1, ATP5B, POU5F1, SOX2 and DNMT3b ). Maturation of COCs with MEHP (20 or 1000 nM) affected gene expression in the mature oocyte. Maturation of COCs with MEHP (20 or 1000 nM) in the absence of estradiol reduced oocyte developmental competence ( P < 0.05). A differential carryover effect on transcript abundance was recorded in blastocysts developed from MEHP-treated oocytes. In the presence of estradiol, increased expression was recorded for CYC1, ATP5B, SOX2 and DNMT3b . In the absence of estradiol, decreased expression was recorded, with a significant effect for 1000 nM MEHP ( P < 0.05). Taken together, the findings suggest that low levels of phthalate must be taken into consideration in risk assessments.